Jocelin of Wells : bishop, builder, courtier - Dunning, Robert W. (Robert William), 1938- (Studies in the history of medieval religion, 2010)
The life and career of Jocelin of Wells examined, with a particular emphasis on his role in the reconstruction of the Cathedral and Bishop's Palace.